2007
DOI: 10.4049/jimmunol.179.9.6297
|View full text |Cite
|
Sign up to set email alerts
|

Nerve Growth Factor Promotes TLR4 Signaling-Induced Maturation of Human Dendritic Cells In Vitro through Inducible p75NTR 1

Abstract: Nerve growth factor (NGF) has been shown to play important roles in the differentiation, function, and survival of immune cells, contributing to immune responses and pathogenesis of autoimmune diseases. Dendritic cells (DCs) are a potent initiator for immune and inflammatory responses upon recognition of pathogens via Toll-like receptors (TLR). However, expression of NGF and its receptors on human monocyte-derived DCs (MoDCs) and the role of NGF in the response of DCs to TLR ligands remain to be investigated. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
20
0
1

Year Published

2008
2008
2020
2020

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 25 publications
(24 citation statements)
references
References 49 publications
3
20
0
1
Order By: Relevance
“…Instead, our work confirms and extends previous findings showing that p75 NTR is able to activate p38 MAPK (12,33). This effect cannot be induced by the NGF neurotrophic receptor TrkA since we have previously demonstrated that blocking antibodies against p75…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…Instead, our work confirms and extends previous findings showing that p75 NTR is able to activate p38 MAPK (12,33). This effect cannot be induced by the NGF neurotrophic receptor TrkA since we have previously demonstrated that blocking antibodies against p75…”
Section: Discussionsupporting
confidence: 92%
“…Neurotrophin binding to p75 NTR has been shown to activate different members of the MAPK family of Ser/Thr kinases, including p38 MAPK (12,33), ERK (70), and c-Jun N-terminal kinase (JNK) (10). In accordance with these latter reports, sustained activation of p38 MAPK in response to NGF was observed to rapidly occur in the nuclear compartment of DCRNs (Fig.…”
Section: Fig 3 E2f4 Acts As a Transcriptional Activator In Dcrns (A)supporting
confidence: 72%
See 1 more Smart Citation
“…), endosome/lysosome-localized molecules (Rab7b, 22,23 CLM-3 24 ), gene transcription coactivators (beta-catenin 25 ), antigen-presenting molecules (MHC I and MHC II 26,27 ), and even HSP70, 28 HSP70L1 29 and NGF. 30 Recently, RIG-I signal pathway regulation was extensively investigated; [31][32][33][34] however, the full anti-inflammatory response mechanisms and the precise finetuning of this process still remain incompletely elucidated.…”
Section: Introductionmentioning
confidence: 99%
“…There is growing evidence to indicate that many molecules have been identified as positive or negative regulators of signaling for these innate receptors. For TLRs, these include membrane molecules (CD11b [8] and PECAM1 [9]), antigen presenting molecules (MHCI [10] and MHCII [11]), ubiquitin related proteins (Nrdp1 [12] and CHIP [13]), phosphatases (SHP-1 [14], SHP-2 [15], SHIP-1 [16] and PTP1B [17]), protein kinases (CaMKII [18]), endosome/lysosome-localized molecules (Rab7b [19,20], CLM [21]), a co-activator of gene transcription (-catenin [22]), HSP70 [23], HSP70L1 [24], and NGF [25]. The regulation of RLR and NLR signal pathways has been extensively investigated recently [26,27]; however, the precise mechanisms of regulation remain to be fully elucidated.…”
mentioning
confidence: 99%